PENGARUH METODE EKSPERIMEN DALAM PERKEMBANGAN KONSEP BERPIKIR SEBAB AKIBAT ANAK USIA DINI PADA KELOMPOK B DI TK PEMBINA LAMBU KOTA BIMA - Wahyu Ningsih, Sri; Martuty, Arie; Sufliati Romba, Sri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the experimental method on the development of the concept of cause-and-effect thinking in early childhood Group B at TK Negeri Pembina Lambu, Bima City. The background of this research is the lack of variation in learning methods that involve direct experience, so that children‘s understanding of causal relationships is not yet optimal. This research uses a quantitative approach with a pre-experimental design type One Group Pretest-Posttest Design. The population in this study were all children in Group B, and the sample was determined using purposive sampling technique totaling 11 children. Data collection techniques used observation and documentation. The data analysis technique used the Wilcoxon Signed Rank Test. The results showed that the average score of children’s cause-and-effect thinking ability increased from 34.45 at the pretest to 47.09 at the posttest, with an increase of 12.64 points. The results of the Wilcoxon test obtained Asymp. Sig. (2-tailed) of 0.003 which is smaller than 0.05, so H0 is rejected and H1 is accepted. Thus, it can be concluded that the experimental method has a significant effect on the development of the concept of cause-and-effect thinking in early childhood Group B at TK Negeri Pembina Lambu, Bima City.